Cord Blood Vitamin D Levels and Early Childhood Blood Pressure: The Healthy Start Study. Issue 9 (7th May 2019) - Sauder, Katherine A.; Stamatoiu, Alexandra V.; Leshchinskaya, Elina; Ringham, Brandy M.; Glueck, Deborah H.; Dabelea, Dana
Abstract : Background: Vitamin D deficiency is associated with cardiovascular events among adults, but it is unclear whether early‐life vitamin D deficiency influences cardiovascular risk factors in children. Methods and Results: We measured total and bioavailable 25‐dihydroxyvitamin D (25OHD) in cord blood and in blood from 4‐ to 6‐year‐old children, and we assessed cardiovascular risk factors (blood pressure, arterial stiffness, body size, and adiposity) at 4 to 6 years. We tested for racial/ethnic differences in total and bioavailable 25OHD (n=715) and modeled the adjusted association between cord blood 25OHD and childhood cardiovascular risk factors (n=171). We observed racial/ethnic differences in total and bioavailable 25OHD levels in both cord and child blood samples (all P <0.05). Each 25‐nmol/L increase in cord blood total 25OHD was associated with a 2.5–mm Hg (SE 0.8) decrease in systolic blood pressure ( P =0.002) and a 1.7–mm Hg (SE 0.6) decrease in diastolic blood pressure ( P =0.01), independent of childhood 25OHD levels, race/ethnicity, and other covariates. There was no association between cord blood total 25OHD and any other cardiovascular risk factors. Cord blood levels of bioavailable and free 25OHD were not associated with any cardiovascular risk factor in childhood. Conclusions: In this diverse prebirth cohort, we observed lower systolic and diastolic blood pressure among children with higher total 25OHD levels at birth. Our findings suggest that intrauterine exposure to vitamin D may contribute to early‐life programming of offspring blood pressure. Intervention studies are needed to determine whether increasing fetal vitamin D exposure can reduce the risk of elevated blood pressure in childhood.